Sigma Chi Fraternity Derby Day celebration at Wake Forest, 1964. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-18-64 p.1.
Sigma Chi Fraternity Derby Day celebration at Wake Forest, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth